2018
DOI: 10.1063/1.5039518
|View full text |Cite
|
Sign up to set email alerts
|

Glassy dynamics of two poly(ethylene glycol) derivatives in the bulk and in nanometric confinement as reflected in its inter- and intra-molecular interactions

Abstract: The inter-and intra-molecular interactions as they evolve in the course of glassy solidification are studied by broadband dielectric-and Fourier-transform infrared-spectroscopy for oligomeric derivatives of poly(ethylene glycol) derivatives, namely, poly(ethylene glycol) phenyl ether acrylate and poly(ethylene glycol) dibenzoate in the bulk and under confinement in nanoporous silica having mean pore diameters 4, 6, and 8 nm, with native and silanized inner surfaces. Analyzing the spectral positions and the osc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 65 publications
(68 reference statements)
2
12
0
Order By: Relevance
“…It should be noted that the work of Alexandris et al is in line with previous studies by Kremer and co-workers, who investigated the dynamics of various liquids in native and functionalized (mainly silanized) silica nanopores and showed that intermolecular interactions between the host and guest materials are key to understand the confinement effect. Unfortunately, similar kinds of investigations in alumina pores are much more difficult to perform, since the silanization of this medium is not as effective as in the case of silica membranes, and the conversion of the hydroxyl units in the former material is quite low. Therefore, to probe the impact of the strength of interactions on the dynamics of liquid confined in alumina membranes, another strategy involving the modification of the chemical structure of the infiltrated compound should be applied.…”
Section: Introductionsupporting
confidence: 63%
“…It should be noted that the work of Alexandris et al is in line with previous studies by Kremer and co-workers, who investigated the dynamics of various liquids in native and functionalized (mainly silanized) silica nanopores and showed that intermolecular interactions between the host and guest materials are key to understand the confinement effect. Unfortunately, similar kinds of investigations in alumina pores are much more difficult to perform, since the silanization of this medium is not as effective as in the case of silica membranes, and the conversion of the hydroxyl units in the former material is quite low. Therefore, to probe the impact of the strength of interactions on the dynamics of liquid confined in alumina membranes, another strategy involving the modification of the chemical structure of the infiltrated compound should be applied.…”
Section: Introductionsupporting
confidence: 63%
“…In this context, it is worthwhile to remind recent atomic force microscopy measurements performed for glycerol incorporated within alumina membranes of d = 10 nm, demonstrating that surface tension and most likely interfacial tension γ SL varies with the surface curvature of applied nanochannels. Moreover, a close correlation between both effects is also well illustrated in the case of the dielectric studies on PPG infiltrated within controlled porous glasses of various pore diameters ( d = 2.5–20 nm). As shown, the glass transition temperature, T g , of infiltrated PPG revealed a nonlinear (parabolic) dependence, where the rise of T g noted for smaller pore diameter ( d < 3 nm) was discussed in terms of the adsorption effects overcoming the confinement one. On the other hand, in the case of various PPG derivatives within silica pores characterized by a little larger pore sizes ( d = 4–8 nm), ,, a linear reduction of T g with increasing degree of confinement was observed for both native and silanized templates. This might indicate that the impact of the surface effects should be often discussed together with the finite size (especially the pore curvatures) which might induce changes in the surface interactions and also should be taken into account to predict the behavior of the confined liquids. …”
Section: Introductionmentioning
confidence: 92%
“…30−32 As shown, the glass transition temperature, T g , of infiltrated PPG revealed a nonlinear (parabolic) dependence, where the rise of T g noted for smaller pore diameter (d < 3 nm) was discussed in terms of the adsorption effects overcoming the confinement one. On the other hand, in the case of various PPG derivatives within silica pores characterized by a little larger pore sizes (d = 4−8 nm), 3,5,6 a linear reduction of T g with increasing degree of confinement was observed for both native and silanized templates. This might indicate that the impact of the surface effects should be often discussed together with the finite size (especially the pore curvatures) which might induce changes in the surface interactions and also should be taken into account to predict the behavior of the confined liquids.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations